Improving Structure Delineation for Radiation Therapy Planning Using Dual-Energy CT - Noid, George; Zhu, Justin; Tai, An; Mistry, Nilesh; Schott, Diane; Prah, Douglas; Paulson, Eric; Schultz, Christopher; Li, X. Allen (Frontiers in Oncology, 2020)
Purpose: We present the advantages of using dual-energy CT (DECT) for radiation therapy (RT) planning based on our clinical experience. Methods: DECT data acquired for 20 representative patients of different tumor sites and/or clinical situations with dual-source simultaneous scanning (Drive, Siemens) and single-source sequential scanning (Definition, Siemens) using 80 and 140 kVp X-ray beams were analyzed. The data were used to derive iodine maps, fat maps, and mono-energetic images (MEI) from 40 to 190 keV to exploit the energy dependence of X-ray attenuation. Advantages of using these DECT-derived images for RT planning were investigated. Results: When comparing 40 keV MEI to conventional 120 kVp CT, soft tissue contrast between the duodenum and pancreatic head was enhanced by a factor of 2.8. For a cholangiocarcinoma patient, contrast between tumor and surrounding tissue was increased by 96 HU and contrast-to-noise ratio was increased by up to 60% for 40 keV MEI compared to conventional CT. Simultaneous dual-source DECT also preserved spatial resolution in comparison to sequential DECT as evidenced by the identification of vasculature in a pancreas patient. Volume of artifacts for five patients with titanium implants was reduced by over 95% for 190 keV MEI compared to 120 kVp CT images. A 367 cm3 region of photon starvation was identified by low CT numbers in the soft tissue of a mantle patient in a conventional CT scan, but was eliminated in a 190 keV MEI. Fat maps enhanced image contrast as demonstrated by a meningioma patient. Conclusions: The use of DECT for RT simulation offers clinically meaningful advantages through improved simulation workflow and enhanced structure delineation for RT planning.